PENGARUH FASILITAS DAN LOKASI PADA NUANSA PANTAI COFFEE TERHADAP KEARIFAN LOKAL (Studi Kasus Masyarakat Desa Cot Keurundong Kabupaten Bireuen) - Amanda, Nadia; Firmansyah, Denny (IndOmera, 2026)
Coastal tourism development has significant economic potential; however, improper management may lead to the erosion of local wisdom within surrounding communities. This condition is evident in the management of Nuansa Pantai Coffe in Cot Keurundong Village, Bireuen Regency, where issues related to facilities and location affect local cultural values. Therefore, this study aims to analyze the influence of facilities and location on community local wisdom. This research applies an associative method with a quantitative approach by distributing questionnaires to 245 respondents. The data were analyzed using multiple linear regressions. The results indicate that facilities and location have a positive and significant effect on local wisdom, both partially and simultaneously. The regression model obtained is Y = 0.146 + 0.375X₁ + 0.197X₂, with an Adjusted R Square value of 0.622. These findings show that facilities have a more dominant influence than location on the preservation of local wisdom.